Inside the world of a football agent - Tedeschi, Gennaro Giulio (Business Expert Press, 2021)
Inside the World of a Football Agent provides a series of practical cases, experienced first-hand by the author, that will help the readers to immerse themselves in the reality of a football agent that interacts with presidents, CEO, sports directors, supporters, footballers, and their families. The audience for the book is represented by all the current or aspiring professionals involved in the football industry: from football agents who want to keep up to date with the latest legislation, to aspiring agents, sports directors or media, who want to understand what is often behind a yes or no i.